2016
DOI: 10.1111/jace.14437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ceramic‐Based Construction and Demolition Waste: Use as Pozzolan in Cements

Abstract: Depending on its composition and properties, construction and demolition waste (C&DW) may be used today as recycled aggregate to manufacture more eco‐efficient concrete, for drainage or as a sub‐base in roads and on occasion as a decorative or esthetic element in pedestrian pathways in parks and landscaped grounds. In Spain, 54% of C&DW is ceramic‐based (CB‐C&DW). Since the use of such waste as recycled aggregate is not envisaged in Spanish legislation, it is presently stockpiled in landfills, an environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 61 publications
3
31
0
3
Order By: Relevance
“…The 859.5 million tonnes of construction and demolition waste (C&DW) generated yearly in the EU alone [4] constitute the largest flow of discarded materials Europe-wide. That waste contains around 54 % by volume of fired clay-based, also called ceramic, materials [5]. Many EU countries are striving to reach 70 % valorisation of such waste by 2020 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The 859.5 million tonnes of construction and demolition waste (C&DW) generated yearly in the EU alone [4] constitute the largest flow of discarded materials Europe-wide. That waste contains around 54 % by volume of fired clay-based, also called ceramic, materials [5]. Many EU countries are striving to reach 70 % valorisation of such waste by 2020 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fired clay industry waste is one of the new pozzolans explored by researchers. A number of prior studies on this material showed that fired clay of different origins has very promising pozzolanic properties because when fired at temperatures of 600°C‐900°C and ground to cement fineness, initially inert clay minerals acquire substantial pozzolanicity . The evaporation of chemically combined water at such temperatures and the resulting breakdown of the crystalline network of clay constituents induces the formation of an amorphous or vitreous material.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s and especially in the last two decades, the international scientific community has researched extensively the viability of reusing C&DW as a raw material in the construction industry, primarily in cement (Asensio et al, 2016), concrete (Akhtar and Sarmah, 2018) and roads (Poulikakos et al, 2017), including studying its inclusion in the respective standards (LNEC-E471 (National Laboratory of Civil Engineering, 2006), EN 12620 (European Committee for Standardization, 2013)) (Tam et al, 2018) or formulating recommendations for its use (RILEM, 1994). If implemented, such measures would remove the barriers to the use of RA.…”
Section: Introductionmentioning
confidence: 99%